Oracle wait interface : a practical guide to performance diagnostics and tuning. - Shee, Richmond, ....-; Deshpande, Kirtikumar, ....-; Gopalakrishnan, K., ....- (New York : McGraw-Hill, 2004)
Troubleshoot, tune, and optimize your Oracle database efficiently and successfully every time. This book explains how to take full advantage of the revolutionary Oracle Wait Interface to quickly pinpoint--and solve--core problems and bottlenecks, and increase productivity exponentially.
Keywords: Database systemen; Oracle; Systeemanalyse